The Armenians of Aintab the economics of genocide in an Ottoman province - Kurt, Ümit 1984- (Harvard University Press, 2021)
Ümit Kurt explores causes and effects of the Armenian genocide in his hometown of Gaziantep, Turkey. He finds that local gentry and ordinary Turks were heavily motivated by the prospect of financial gain as Armenians were dispossessed. Newly enriched Turks then financed the young republic, elevating themselves to the status of a political elite.